If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4m = 5(m + 1) Reorder the terms: 6 + 4m = 5(1 + m) 6 + 4m = (1 * 5 + m * 5) 6 + 4m = (5 + 5m) Solving 6 + 4m = 5 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 6 + 4m + -5m = 5 + 5m + -5m Combine like terms: 4m + -5m = -1m 6 + -1m = 5 + 5m + -5m Combine like terms: 5m + -5m = 0 6 + -1m = 5 + 0 6 + -1m = 5 Add '-6' to each side of the equation. 6 + -6 + -1m = 5 + -6 Combine like terms: 6 + -6 = 0 0 + -1m = 5 + -6 -1m = 5 + -6 Combine like terms: 5 + -6 = -1 -1m = -1 Divide each side by '-1'. m = 1 Simplifying m = 1
| 3y+2x=2(y-2x) | | 6(x+9)=8x+8-2x+46 | | 63(5x+4/9)=6(50x-1/3) | | 10+3n=14 | | 6x-9=6(x+9) | | 0.5(x+100)=0.58x-574 | | -16t^2+24t=0 | | 6x-4y=7 | | N/-2=8 | | -4=-10/86+8 | | (7x^3*(2x^2)^2)/(10x^5) | | 3.4x=2.6x+5.6 | | (x/9)=(x/10)-8 | | x/9=x/10-8 | | 100(2+x)=100 | | (x-1)3+64=0 | | f(x)=-2x^2+5x+40 | | 10(z+2)-2(z-2)=3(z-3)+4(z-1) | | 0.4(0.7-4x)=-1.1x | | 459x+1377-23=8x+160 | | R/-6=-4 | | x^6/5-729=0 | | 50=-2(23-y)+4(y-3) | | v^2+15v+56= | | 2(x+1)(x-1)-(2x+3)(x-2)=0 | | 12m=56+12m | | x^3-4x^2-x-10=0 | | 14x^2=16 | | 4(t+1)=6-1 | | (x+7)2=100 | | -64=-8v | | 18-4x+6=x+9 |